Wogonin Hampers Dexamethasone-Induced Oxidative Imbalance in Sprague Dawely Rats - Maha Magdy Hassanin; Mai Tolba; Marianne Tadros; Mohamed Elmazar; Abdel-Nasser Singab (Ain Shams University, 2020)
Corticosteroids are frequently used for their powerful anti-inflammatory activity in the management of various chronic inflammatory diseases. They are also used because of their potent immunosuppressive power in the manipulation of adverse effects associated with chemotherapeutic treatments. However, their long-term usage is associated with several side effects. The majority of these side effects are due to the increased oxidative stress associated with their administration. Dexamethasone (DEX) is one of the most commonly used glucocorticoids either as an anti-inflammatory and/or immunosuppressive agent.Wogonin, a mono-flavonoid present in the root of Scutellaria baicalensis Georgi, has attracted considerable attention in recent years. Wogonin has a well-documented antioxidant activity that is mainly responsible for its multiple pharmacological activities. The current study aimed at investigating the possible protective activity of wogonin against DEX-induced oxidative stress in Sprague Dawley rats. The results showed that wogonin co-treatment successfully counteracted DEX-induced oxidative stress. Co-administration of wogonin doses of 30 and 60 mg/kg/day significantly improved superoxide dismutase (SOD) activity by 1.7 (P<0.001) and 3.9 folds (P<0.001) and significantly improved catalase (CAT) activity by 1.9 and 2.2 folds (P<0.05) as compared to DEX group. Moreover, co-treatment with wogonin (30 mg/kg/day) improved reduced glutathione (GSH) level by 1.5 folds, while the higher dose significantly improved GSH level by 2.3 folds (P<0.05) as compared to DEX group. Also, co-treatment with wogonin improved serum malondialdehyde MDA level by 11.8% and 30% compared to the DEX group. In conclusion, wogonin displayed a promising protective antioxidant effect against DEX-induced oxidative stress.